(untitled) (Global Journal of Computer Science and Technology, 2013)
Most researches have been done for past few decades on distributed sensor and also fabricating the fibre optic to make sensor to detect vibration cracks on the building and environmental factors Due to the fact that fibre optic sensors are small electrically isolated and immune to electromagnetic fields they are an adequate choice to incorporate into the composite material designs In this study the transmission losses due to pressure on an optical fiber to determine the pressure sensitivity were investigated using a commercial optical time domain reflectometer OTDR A multimode optical fiber 50 125 was subjected to pressure using various mass in the range of 500 g to 2000 g at 25 m and 50 m from the end of the fiber The mass was placed on the fiber using microbend test rigs The sensor with an area 910 x 10-6 m2 with corrugation periodicity 2 mm for sensor I and 1 6 mm for sensor II was constructed The Optical signal of 1300 nm from the OTDR was transmitted along a fiber of length of 1173 5 m The optical output is analyzed using OTDR Trace Viewer 4 1 and the transmission losses were determined by two point loss and combination loss methods The transmission loss increases with increase in pressure and increases with increase in sensor placement from the end of an optical fiber towards the transmitter The sensor sensitivity remain constant at 25 m and 50 m determined by two point loss method with the value of 3 x10-4 dB Pa for sensor I and 4 x 10-4 dB Pa for sensor II However the sensor sensitivity increases to 5 x 10-4 dB Pa for sensor I and to 11 x 10-4 dB Pa for sensor II when sensors were placed at 50 m Therefore the sensor II is more sensitive than I due to more microbendings